JOB AUTONOMY, JOB CRAFTING AND EMPLOYEES’ WELL-BEING DURING WORKING FROM HOME - Susanti Saragih; Meily Margaretha; Luthfia Anantyanda (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2021)
Workplace stressed employees’ well-being because people have to work from home (WFH) and adapt to a new routine of work and life since Covid-19 struck the world. Employees who WFH increase their perception of more autonomous on how to handle their tasks, this is known as job autonomy. This study aimed to examine the relationship between job autonomy and well-being, and the mediating effects of job crafting on job autonomy and employees’ well-being during WFH in Covid-19 Pandemic. An online survey was conducted and there were 427 respondents involved. The model was analyzed using WarpPLS 7.0 and the results showed that no significant relationship was found between job autonomy and well-being. Moreover, job autonomy and job crafting are related as well as job crafting and well-being. Job crafting significantly mediate the relationship between job autonomy and well-being. This study showed that during WFH, employee experience an excessive degree of job freedom and it give them more work pressure and decrease employees' subjective well-being. In a conclusion, this study brings several concerns that organizations should be giving attention to.